Evaluating the role of neoadjuvant chemotherapy in bladder cancer patients with occult lymph node metastases - Moschini, Marco; Zamboni, Stefania; Mattei, Agostino; Martini, Alberto; Zaffuto, Emanuele; Briganti, Alberto; Gallina, Andrea; Montorsi, Francesco (Translational Andrology and Urology, 2018)
Bladder cancer (BCa) is the second most common genitourinary malignancy with 81,190 estimated new diagnosis in the 2018 in the United States only (1). Radical cystectomy (RC) with bilateral pelvic node dissection (PLND) represents the gold standard for very recurrent high risk non-muscle invasive tumors and for muscle invasive BCa (2).